1978
DOI: 10.1073/pnas.75.2.710
|View full text |Cite
|
Sign up to set email alerts
|

Discrete length classes of DNA depend on mode of dehydration.

Abstract: The length of double-stranded coliphage X DNA, as determined by electron microscopy using the benzyldimethylalkyl ammonium chloride technique, depends on the mode of dehydration. The freeze-dried DNA form is the longest (16.5 mr), whereas dehydration in methanol (15.9 Am) or in ethanol (three forms: 15.2 gsm, 13.9 im, and 12.4 gm) results in progressively shorter molecules. These measured lengths of the freeze-dried, methanol-dehydrated, and shortest ethanol-dehydrated forms correspond to the axial rise per nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The same RNA polymerase distribution is shown by TEM in figure 2B. Under our experimental conditions, the DNA template has lost its supercoiled form in most cases as described in electron microscopic studies (Vollenweider et al 1978); however, this conformational change did not affect the protein binding. This result indicates that DNA is still flexible during the alcoholic process and goes through successive forms after its adsorption on mica surface.…”
Section: Resultssupporting
confidence: 78%
“…The same RNA polymerase distribution is shown by TEM in figure 2B. Under our experimental conditions, the DNA template has lost its supercoiled form in most cases as described in electron microscopic studies (Vollenweider et al 1978); however, this conformational change did not affect the protein binding. This result indicates that DNA is still flexible during the alcoholic process and goes through successive forms after its adsorption on mica surface.…”
Section: Resultssupporting
confidence: 78%
“…After correction for lengthening of the DNA by 2.7 A per bound ethidium (Hogan et al, 1979) (r -0.06; 140 base pairs; 0 = 41°), the calculated DNA length per base pair is 3.91 A when L -430 A and is 2.86 A when L = 320 A. The former number is clearly outside the range of plausible values as judged, for example, by electron microscopy (Vollenweider et al, 1978;Griffith, 1978). Taking 3.4 A to be the maximum allowed rise per base pair, we estimate a maximum value of L = 377…”
Section: Discussionmentioning
confidence: 85%
“…Along this line, Girod et al reported that in the range of 0–65% EtOH (v/v), the CD changes reflect a DNA B-to-C transition . The progressive dehydration results in stepwise shrinkage from the B form to the progressively shorter C-forms . By comparison with the B form, C-DNA structures display considerably more inclination, destacking, and displacement of the bases toward the major groove.…”
Section: Introductionmentioning
confidence: 96%